Diet from Mantisa religiosa-egg case abolishes pulmonary dysfunctions triggered by sub-acute exposure to aerosolized-petroleum hydrocarbons in rat model. (August 2019) - Akintunde, J.K.; Obisesan, O.O.; Akinsete, S.J.; Adegoke, A.M.
Summary: Daily exposure to fractionated petroleum products could be connected to respiratory disorders in industrialized countries and insectary egg of high proteins may be applied as the diet for its management. This study checked the effect of dietary supplemented Mantisa religiosa egg case (DSMREC) on pulmonary dysfunctions triggered by sub-acute exposure to petroleum hydrocarbons in the animal model. Animals were divided into eight groups (n = 8): control group; normal rats exposed to 15 ml aerosolized kerosene, petrol, and diesel, respectively for 1hr daily for 14 days; positive control rats treated with 4% DSMREC only; rats exposed to 15 ml aerosolized kerosene, petrol, and diesel, respectively and co-treated with 4% DSMREC. The results elevated lung ADA, 5 1 -nucleatidase activities and MDA content following exposure to aerosols of petroleum hydrocarbons. Also, aerosols thickened the pulmonary interstitial cells, distended alveoli (emphysema), proliferated bronchial associated lymphoid tissues followed by the congestion of pulmonary blood vessels. Amazingly, 4% DSMREC prevented these alterations. Therefore, our results suggest some possible mechanisms of action by which 4% DSMREC prevents petroleum-induced pulmonary toxicity in rats.